Quantification of microbial communities in subsurface marine sediments of the Black Sea and off Namibia - Schippers, Axel; Kock, Dagmar; Höft, Carmen; Köweker, Gerrit; Siegert, Michael (Frontiers in Microbiology, 2012)
Organic-rich subsurface marine sediments were taken by gravity coring up to a depth of 10 m below seafloor at six stations from the anoxic Black Sea and the Benguela upwelling system off Namibia during the research cruises Meteor 72-5 and 76-1, respectively. The quantitative microbial community composition at various sediment depths was analyzed using total cell counting, catalyzed reporter deposition – fluorescence in situ hybridization (CARD–FISH) and quantitative real-time PCR (Q-PCR). Total cell counts decreased with depths from 109 to 1010 cells/mL at the sediment surface to 107–109 cells/mL below one meter depth. Based on CARD–FISH and Q-PCR analyses overall similar proportions of Bacteria and Archaea were found. The down-core distribution of prokaryotic and eukaryotic small subunit ribosomal RNA genes (16S and 18S rRNA) as well as functional genes involved in different biogeochemical processes was quantified using Q-PCR. Crenarchaeota and the bacterial candidate division JS-1 as well as the classes Anaerolineae and Caldilineae of the phylum Chloroflexi were highly abundant. Less abundant but detectable in most of the samples were Eukarya as well as the metal and sulfate-reducing Geobacteraceae (only in the Benguela upwelling influenced sediments). The functional genes cbbL, encoding for the large subunit of RuBisCO, the genes dsrA and aprA, indicative of sulfate-reducers as well as the mcrA gene of methanogens were detected in the Benguela upwelling and Black Sea sediments. Overall, the high organic carbon content of the sediments goes along with high cell counts and high gene copy numbers, as well as an equal abundance of Bacteria and Archaea.